1985
DOI: 10.1111/j.1469-8749.1985.tb03773.x
|View full text |Cite
|
Sign up to set email alerts
|

KINESTHETIC RECALL OF CHILDREN WITH ATHETOID and SPASTIC CEREBRAL PALSY and OF NON‐HANDICAPPED CHILDREN

Abstract: SUMMARY Twenty‐four children with spastic or athetoid quadriplegic cerebral palsy were paired according to severity of motor disability and age, then matched with 12 non‐handicapped children of similar ages. The children were tested with a standard kinesthesiométér and two kinds of scores were recorded. Absolute Error scores reflected the children's deviation from the target and Total Movement scores reflected their over‐all range of movement. There were significant differences between groups in Absolute Error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Sensory mechanisms are known to be disturbed in children with CP, e.g. twopoint discrimination, stereognosis and kinaesthetic sensitivity (Lesny 1971, Bairstow and Laszlo 1981, Opila-Lehman et al 1985, Uvebrant 1988). There is also evidence of disturbed proprioreception, tested by means of tonic muscle vibrationactivating la afferents (Tardieu et al Ln N N 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Sensory mechanisms are known to be disturbed in children with CP, e.g. twopoint discrimination, stereognosis and kinaesthetic sensitivity (Lesny 1971, Bairstow and Laszlo 1981, Opila-Lehman et al 1985, Uvebrant 1988). There is also evidence of disturbed proprioreception, tested by means of tonic muscle vibrationactivating la afferents (Tardieu et al Ln N N 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a possible peripheral mechanism involves a change in directed attention to the intact sensory feedback (i.e., vision) instead of distorted sensory feedback (i.e., proprioception). Indeed, for individuals with hemiparesis, it has been suggested that redirection of visual attention toward the sensory feedback of the more impaired arm might help individuals with hemiparesis to reduce movement disorders and future complications such as learned disuse (Sathian, Greenspan, & Wolf, 2000;Opila-Lehman, Short, & Trombly, 1985). The "mirror box" is thought to assist with the switch in attention because the visual signals received back from the superimposed image seen in the mirror correspond with the movements of the less impaired arm.…”
Section: Discussionmentioning
confidence: 99%
“…Methods used in prior studies of proprioception in CP primarily were clinically-based, typically yielded nominal data, and often did not include a control or comparison group. Only 1 study assessed joint-position sense, where participants matched elbow joint position to a remembered position 6. Kinesthesia, studied to a greater extent than joint-position sense, has typically been assessed by having participants determine the direction of a passively moved limb (eg, “Did your toe move up or down?”) without controlling for force of cutaneous contact or limb-movement displacement and velocity 4,7-15.…”
mentioning
confidence: 99%